Comparative Analysis of Intestinal Characteristics of Largemouth Bass (Micropterus salmoides) and Intestinal Flora with Different Growth Rates - Xin Su (Fishes, 2022)
To explore the causes of different growth rates among juvenile populations of largemouth bass, in the present study, a batch of largemouth bass juveniles reared under the same conditions were divided into a fast-growing group and a slow-growing group. We used histological, enzymatic and molecular biology methods to analyze and determine their histomorphological changes, digestive enzyme activity and intestinal floral composition. The fast-growing group had a significantly (p ≤ 0.01) greater intestinal fold height and muscle thickness than the slow-growing group. Lipase activity was significantly (p ≤ 0.01) higher in the fast-growing group than in the slow-growing group. Intestinal microbial analysis showed that the relative abundance of Actinobacteria and Halomonas in the fast-growing group was higher than that in the slow-growing group. This research shows that the differentiation of growth rates in juvenile largemouth bass populations is closely related to intestinal fold status, lipase activity, and intestinal flora.